Differential nest-defense to perceived danger in urban and rural areas by female Eurasian sparrowhawk (Accipiter nisus) - Kunca, Tomas (PeerJ, 2016)
The reaction of wildlife to humans is known to differ with surroundings. In urban environments that provide suitable habitats for breeding birds, animals adapt to humans and their response is accordingly altered. This study examined the nest defense behavior of female Eurasian sparrowhawks (Accipiter nisus) during the breeding season in urban and rural areas of Prague. The females showed four different types of reaction to humans that approached the nest and differed significantly between the two study areas. Contrary to expectations, urban nesting females were more aggressive than rural conspecifics. The intensity of response increased as the season progressed, and females defended their broods to a much greater degree than their clutches in both urban and rural habitats, suggesting a differential effort as a function of their relative investment in the breeding attempt conforming with the parental investment hypothesis.